Morbidity and mortality weekly report, Vol. 17, no. 5 Week ending February 3, 1968 - Communicable Disease Center (U.S.); United States Dept. of Health, Education, and Welfare Public Health Service; United States Bureau of Disease Prevention and Environmental Control
Table 1. Cases of specified notifiable diseases: United States -- Table 2. Notifiable diseases of low frequency -- Table 3. Cases of specified notifiable diseases: United States for weeks ended February 3, 1968 and Februay 4, 1967 (5th week) -- Table 4. Deaths in 122 United States cities for week ended February 3, 1968 Current trends: Measles - United States -- Measles - Rhode Island -- Measles - Chicago -- Influenza in five U.S. cities International notes: Influenza - Rotterdam, The Netherlands Figure 1. Counties or health districts reporting a total of 10 or more cases of measles December 31, 1967 through January 27, 1968 -- Figure 2. Counties or health districts reporting a total of 10 or more cases of measles January 1 through January 28, 1967 -- Figure 3. Reported cases of measles by month of onset, Rhode Island - October 1966 - December 1967 -- Figure 4. Pneumonia-influenza mortality, influenza in five U.S. cities 1966-67 and 1967-68 -- Figure 5. Influenza, Rotterdam, The Netherlands 1965, 1966 and 1967